RELIGIOUS ADHERENCE AND GOOD CITIZENSHIP: A SYSTEMATIC REVIEW OF THEIR DYNAMIC INTERPLAY IN CONTEMPORARY SOCIETY - JOEMSITTIPRASERT, Watcharin; BUNMON, Panisa; VIPAPORN, Tanapon; KUMAR, Vinay (Thai Arts and Culture Review, 2025)
This systematic review investigates the complex relationship between being a "good religious adherent" and a "good citizen" in contemporary society. Drawing on 21st-century empirical literature from diverse academic databases (Scopus, WoS, PubMed, JSTOR, TCI, and Google Scholar) across multiple disciplines—including philosophy, religious studies, political science, sociology, anthropology, and psychology—this study synthesizes definitions, measurements, and the dynamic interplay of these constructs. Findings reveal both roles are multidimensional and context-dependent. While religiosity frequently correlates positively with prosocial and civic behaviors, this relationship is neither universal nor straightforward, and moral frameworks and social networks mediate it. The study highlights that non-religious individuals can exhibit high civic engagement, and certain forms of intense religiosity may lead to intolerance. Key moderating factors include religiosity type, socio-political context, and religious diversity. We emphasize fostering inclusive religious interpretations and integrating religious values with democratic principles to harness religion's potential for societal good while mitigating its divisive tendencies. Future research should prioritize longitudinal and cross-cultural investigations into underlying mechanisms and the impact of contemporary social changes.